Direct Participation in Hostilities and Respect for the Lives of Civilians During Armed Conflicts .......... 455 - Marcinko, Marcin (Promoting Changes in Times of Transition and Crisis: Reflections on Human Rights Education, 2013)
During an armed conflict there may be a situation when a civilian becomes actively involved in hostilities, and since this is in contradiction with the international humanitar-ian law of armed conflict. By doing so, such person risks being deprived of protection they otherwise deserve and may become the target of enemy assault. Here, however, appears a problem: since the international humanitarian law does not provide a precise definition of “direct participation in hostilities” and fails to specify what activities may be described as connected with or forming its part. An attempt was made by the International Committee of the Red Cross to provide the above definition in Interpretive Guidance on the Notion of Direct Participation in Hostilities under International Humanitarian Law (published in 2009). Despite numerous critics, the foregoing document should be considered as es-sential and necessary especially at the time of the “war against terrorism” or in the case of the so-called asymmetric conflicts. By defining three obligatory prerequisites that must be met in order for an event to qualify as “direct participation in hostilities”, the International Committee of the Red Cross more clearly specified the case of “direct participation in hostilities”, putting an end to free choice of interpretation that may cause death of innocent or neutral persons not involved in warfare actions. Accurate interpretation of the above-referred notion – which is the core topic of the present article – may contribute to more effective protection of civilians against direct attacks and help enforce respect for their life during an armed conflict.